REPRODUCTION BIOLOGY OF GOLDBAND GOATFISH Upeneus moluccensis Bleeker, 1855 IN SUNDA STRAIT - Herman Sarumaha; Rahmat Kurnia; Isdradjad Setyobudiandi (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
This research was to analyze the reproduction biology of the goldband goatfish in the Sunda Strait as a reference for appropriate and sustainable management. Sampling was collected from April to August 2015. The samples from Sunda Strait were obtained from the fisherman yielded in the Coastal Fishing Port Labuan, Pandeglang, Banten Province. The sample was analyzed in Fisheries Biology Laboratory, Aquatic Resources Management Department, Fisheries and Marine Science Faculty, Bogor Agricultural University. Fish samples were measured, weighed and dissected, then morphologically observed for the reproductive organs. Samples obtained during the research were 811 specimen with the total length of 82-219 mm. Sex ratio among females and males were 1.5:1. The size at first maturity of females and males were 124 mm and 120 mm, respectively. Females were dominated by gonad maturity stage III and I, while for males dominated by gonad maturity stage I and II. Based on the composition of the TKG and IKG values each month, spawning season of the goldband goatfish in the Sunda Strait occurred in April and August. Fecundity obtained ranged 955-59.356 eggs with partial spawning type.